1988
DOI: 10.1002/art.1780310118
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 activates phospholipase a2 IN HUMAN SYNOVIAL CELLS

Abstract: Interleukin-1 (IL-1) treatment of synovial cells from rheumatoid arthritis and osteoarthritis patients resulted in a dose-dependent secretion of phospholipase A2 (PLA2). IL-1 also stimulated prostaglandin E2 and plasminogen activator synthesis, in parallel with PLA2 activation; all 3 were detectable within 6 hours of IL-1 treatment and peaked by 24 hours. Synovial cell PLA2 required calcium (5 mM) and a neutral pH (7.5) for maximal activity and appears similar to the PLA2 in synovial fluid, which has been desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
3
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 11 publications
2
31
3
1
Order By: Relevance
“…We found a statistically significant rise in the activity of PLA, in joint fluids from valgus-operated knee joints at 7 months, but not at 18 months after operation. PLA, originates from the synovial lining cells, inflammatory cells or chondrocytes (Gilman et al 1988, Gonzales-Buritica et al 1989, Pruzanski et al 1990). Increased mechanical stimulation as a signal for initiation of PLA, production by the chondrocytes has been suggested by Chrisman and co-workers (1981).…”
Section: Discussionmentioning
confidence: 99%
“…We found a statistically significant rise in the activity of PLA, in joint fluids from valgus-operated knee joints at 7 months, but not at 18 months after operation. PLA, originates from the synovial lining cells, inflammatory cells or chondrocytes (Gilman et al 1988, Gonzales-Buritica et al 1989, Pruzanski et al 1990). Increased mechanical stimulation as a signal for initiation of PLA, production by the chondrocytes has been suggested by Chrisman and co-workers (1981).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 and tumor necrosis factor-a have been reported to increase the expression and activity of secretory phospholipase A, in human synovial cells [23], human hepatoma cells [14], and cells from different species 124-261. However, in all of these studies activation was performed by stimulating cells with cytokines especially interleukin-lp, interleukin-6 and tumor necrosis factor-a.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced levels of the cytokine, interleukin (IL)-1␤, 1 perpetuate the disease process through up-regulation of a multitude of factors leading to eicosanoid formation, matrix degradation, bone resorption, and proliferation in the joint (2)(3)(4)(5)(6). We and others have demonstrated that human rheumatoid synovial fibroblast (RSF) prostaglandin (PG) E 2 accumulation in response to IL-1␤ is a direct result of the coordinate up-regulation of 85-kDa phospholipase A 2 (PLA 2 ) and the induction of COX II (6 -8).…”
mentioning
confidence: 99%